DEPTOR modulates activation responses in CD4+ T cells and enhances immunoregulation following transplantation. Issue 1 (17th August 2018) - Wedel, Johannes; Bruneau, Sarah; Liu, Kaifeng; Kong, Sek Won; Sage, Peter T.; Sabatini, David M.; Laplante, Mathieu; Briscoe, David M.
Abstract : DEPTOR is an evolutionarily conserved cell‐intrinsic binding partner of mTOR that functions as a negative regulator of signaling responses. In this study, we show that DEPTOR is expressed within CD4 + T cells, and we observed that its relative level of expression modulates differentiation as well as glucose utilization within CD4 + T effectors in vitro. Using knock‐in mice, we also find that induced expression of DEPTOR within CD4 + T regulatory cells stabilizes Foxp3 expression, shifts metabolism toward oxidative phosphorylation, and increases survival and suppressive function. In vivo, fully MHC mismatched cardiac allograft survival is significantly prolonged in knock‐in recipients and sustained recipient expression of DEPTOR in combination with costimulatory blockade induces long‐term graft survival. Furthermore, we show that the induced expression of DEPTOR in CD4 + T effectors fails to inhibit acute allograft rejection. Rather, prolonged survival is dominantly mediated via induced expression and function of DEPTOR within recipient CD4 + T regulatory cells. These collective findings identify DEPTOR as a novel protein that functions in CD4 + T cells to augment immunoregulation in vitro and in vivo. Abstract : The authors show that CD4 + T cells express DEPTOR and that its primary function is to increase oxidative metabolism and Foxp3 gene activity in regulatory T cells, resulting in augmented stability and function in vitro and in vivo.